Leaf Micromorphology and Internal Anatomy of the Philippine Endemic and Endangered Species Litsea litensis Merr (Batikuling) in Baybay Leyte. - De Sagun, Janice V.; Tan, Irene L. (Tacloban City Janice V. De Sagun, 2013)
Litsea leytensis Merr is one of the endangered and endemic species found in the Philippnes. Studies have been conducted on the propagation, domestication, protection, and conservation of this species, but none on its biology which involves leaf micromorphology and internal anatomy. This study is the first attempt to characterize and identify this species at a cellular level. The descriptions and implications of the structures found were based on published research articles and journals. Leaf micromorphology was revealed using scanning electron microscopy. SEM micrographs showed cuticle coated adaxial epidermal layer, compactly arranged epidermal cells on the abaxial layer, anomocytic and hypostomatic type of stomata, hook-like bristles, and non-glandular unicellular type of trichomes on the abaxial side. For leaf internal anatomy, young and mature leaf samples were subjected to free-hand sectioning and Tolouidine Blue O staining techniques. In the leaf lamina cross section, dorsiventral mesophyll was found in between the upper and lower epidernises. Dispersed in the mesophyll layers are minor veins and isolated large oil cells. The midrib region of the cross section is comprised of angular collenchyma cells, thin-walled parenchyma cells, thickly lignified sclerenchyma cells, and bicollateral vascular bundles. The presence of hypostomata, epicuticular waxes, and isolated oil cells classify this species under Lauraceae family. The results of this study serve as baseline and only information on the leaf micromorphology and internal anatomy of L. leytensis.
Undergraduate thesis (B.S. Biology)--University of the Philippines, Tacloban